On Q-Compactness in Intuitionistic Fuzzy Topological Spaces (Journal of Bangladesh Academy of Sciences, 2020)
In this paper, two new notions of Q-compactness in an intuitionistic fuzzy topological space has been introduced. These two notions satisfy hereditary and productive property. Also it is shown that under some conditions Q-compactness preserved under continuous, one-one and onto function. Further some of their features have been introduced.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 197-203, 2019